Impact of human mobility and weather conditions on Dengue mosquito abundance during the COVID-19 pandemic in Hong Kong - Yufan Zheng; Keqi Yue; Eric W.M. Wong; Hsiang-Yu Yuan (Infectious Disease Modelling)
Background: While Aedes mosquitoes, the Dengue vectors, are expected to expand due to climate change, the impact of human mobility on them is largely unclear. Changes in human mobility, such as staying at home during the pandemic, likely affect mosquito abundance. Objectives: We aimed to assess the influence of human mobility on the abundance and extensiveness of Aedes albopictus, taking account of the nonlinear lagged effects of weather, during the COVID-19 pandemic in Hong Kong. Methods: Google human mobility indices (including residential, parks, and workplaces) and weather conditions (total rainfall and mean temperature) along with Aedes albopictus abundance and extensiveness, monitored using Gravidtrap were collected between April 2020 and August 2022. Distributed lag non-linear models with mixed-effects models were used to explore their influence in three areas of Hong Kong. Results: Time spent at home (i.e., residential mobility) was negatively associated with mosquito abundance. The model projected that if residential mobility in 2022 was returned to the pre-pandemic level, the mosquito abundance would increase by an average of 80.49 % compared to actual observation. The relative risk (RR) of mosquito abundance was associated with low rainfall (<50 mm) after 4.5 months, peaking at 1.73, compared with 300 mm. Heavy rainfall (>500 mm) within 3 months was also associated with a peak RR of 1.41. Warm conditions (21–30 °C, compared with 20 °C) were associated with a higher RR of 1.47 after half a month. Discussion: Human mobility is a critical factor along with weather conditions in mosquito prediction, and a stay-at-home policy may be an effective intervention to control Aedes albopictus.